Socioeconomic Effect of the Scourge of Banditry in Niger State, Nigeria - Odalonu, Boris Happy (Innovare Journal of Education, 2023)
This study examined the socioeconomic effect of banditry in Niger State, Nigeria. The study adopted a survey research design. The data for the study were collected from primary and secondary sources. The content-analysis technique was adopted to analyze and categorize the data collected into key themes of the study. The study is anchored on situational action theory that explicated the reasons behind the rising banditry in Niger State. Findings revealed that the drivers of banditry in Niger State were attributed to poverty, unemployment, large swathes of ungoverned forest reserves, thriving illegal mining activities, the porosity of borders, proliferation of arms and a weak security system. It also revealed that banditry activities have led to the displacement of residents, payment of huge ransoms, abandonment of means of livelihood, and shortage of food and have triggered an adverse socioeconomic crisis for the people. Based on the findings, the study recommended that the ungoverned forests where the bandits operate need to be combed by the military personnel through an air raid and community policing should be established and equipped with security tools to enable them to secure the various communities against banditry, Nigerian porous borders should be blocked to prevent the influx of foreign criminal elements and bandits into the country, the security agencies manning the borders should be strengthened and technologies such as closed circuit cameras, drones, and other technologies should be deployed at the borders to enhance maximum security and more security personnel should be deployed to rural communities that are mostly affected by the activity of bandits.